EFFECTIVENESS OF PUBLIC PARTICIPATION PROGRAMME: A FEEDBACK FROM PARTICIPANTS (SABAK BERNAM DISTRICT LOCAL PLAN AND KUALA LUMPUR STRUCTURE PLAN) - Omar, Dasimah; Hoon Leh, Oliver Ling (PLANNING MALAYSIA, 2007)
Nowadays, public awareness on the potential dangers of environmental problems and the negative impact from the development has been increasing. Public has the right to know and participate in making decisions, particularly in those have potentially affect on the communities in which they live and work. Furthermore, Malaysia is adopting the Rio Declaration - Sustainable Development and Agenda 21. One of the fundamental prerequisites for the achievement of sustainable development is broad public participation in decision-making. Research had been carried out to identify the effectiveness of the public participation programme for Sabak Bemam District Local Plan 2002-2015 and Kuala Lumpur Structure Plan 2020. The research was carried out by collecting feedback from the participants of public exhibitions and workshops for both of the plans. Through the research, it was found that series of workshops are the effective method of public participation for development plan as compared to public exhibition after draft proposal of the plan has been completed. An effective and successful public participation programme should allow members of the community to have an active voice in the process and to have a free access to important information.